Steam Pyrolysis of Oil Sludge for Energy-Valuable Products; Applied Sciences; Vol. 12, iss. 3 - Larionov K. B. Kirill Borisovich; Kaltaev A. Albert; Gvozdyakov D. V. Dmitry Vasilievich; Zenkov A. V. Andrey Viktorovich; Kirgina M. V. Mariya Vladimirovna; Bogdanov I. A. Ilya Aleksandrovich; Slusarskiy (Slyusarsky) K. V. Konstantin Vitalievich; Gubin V. E. Vladimir Evgenievich (2022, 2022)
Title screen